TAWARRUQ PRACTICE FOR LIQUIDITY MANAGEMENT IN ISLAMIC MONEY MARKET IN INDONESIA AND MALAYSIA (Equilibrium: Jurnal Ekonomi Syariah, 2013)
The fast development of Islamic banking and finance in the global market in the last two decades has been raised some issues especially the issue of lack of the product for liquidity management. High demand for Islamic banking and finance it impact high innovation of products and services. Since the business of banking merely related to funding and financing that is also relevant to Islamic banking and intermediary institution, the issue of surplus position and deficit position it has to covered by the product that manage this liquidity issues. The main purpose of this paper is to review the tawarruq that being practiced as Islamic money market instrument in Indonesia and Malaysia that used by Islamic financial institution for liquidity management. In 2011, Jakarta Future Exchange has launched one instrument for Islamic bank as liquidity management instrument namely Komoditi Syariah. This product has some features differences with Bursa Suq Al-Sila Malaysia which launced in 2009, nevertheless they are using the same Islamic contract that is commodity murabahah or known as tawarruq. This paper found that there are some shariah potential issues that affect the compliancy of the product. The paper tries to put some shariah issues in the structures that should be taken into consideration for future shariah structure in liquidity risk management in Islamic banking industries. Therefore, Islamic bank, Islamic stock exchange institutions and other Islamic financial that offer Islamic financial services may take into concern what are shariah parameters in apppling tawarruq structure in any product and services in Islamic bank. Kata kunci: Liquidity Management, Tawarruq, Komoditi Syariah, Bursa Suq Al-Sila